THE IMPORTANCE OF GENERATION Z IN PRESERVING PANCASILA VALUES IN SELAYANG VILLAGE - Sri Rejeki Simbolon; M. Chaerul Rizky; Gloria Florecita Nainggolan; Riska Amelida Hasibuan; Nailah Insyrooh (RADJA PUBLIKA, 2025)
This study aims to examine the role of generation z in preserving Pancasila values ​​in Selayang Village and the factors that influence it. The method used is a quantitative survey involving 125 generation z respondents aged 15-22 years, combined with in-depth interviews and focus group discussions (FGD) to obtain enriched qualitative data. Quantitative data were analyzed using descriptive statistics and compound correlations while qualitative data and thematic analysis. the results of the study indicate that generation z has a high understanding of Pancasila values, but the application of these values ​​in everyday life still needs to be improved. Understanding Pancasila values ​​in involvement in social activities is significantly positively related to the preservation of values ​​while the influence of social media shows a significant negative correlation. Generation z is active in various social and religious activities as a form of preserving values, but participation in creating educational content on social media is still low. This study recommends strengthening applicable Pancasila values ​​education, education on the wise use of social media, and increasing gen z involvement in social religious activities to support the preservation of Pancasila values ​​optimally.